Teachers’ Perceptions of Student Motivation and Its Influence on Assessment Validity in Junior High Schools in South Sulawesi - Muhammad Tahir (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
Abstract This study explores junior high school teachers’ perceptions of student motivation and its influence on assessment validity in South Sulawesi, Indonesia. Grounded in Self-Determination Theory and Expectancy-Value Theory, the research investigates how teachers understand and integrate motivational factors into their assessment practices. A total of 100 teachers participated in a quantitative descriptive survey using a structured Likert-scale questionnaire consisting of 10 items. The data were analyzed using descriptive statistics, including frequency and percentage distributions, and visualized through line and bar charts. The results reveal a strong consensus among teachers that student motivation significantly affects the accuracy and fairness of assessment outcomes. Most respondents agreed or strongly agreed that motivated students perform better and produce more valid results. However, a small proportion of teachers expressed uncertainty regarding how to factor motivation into assessment interpretation, particularly when dealing with low-motivation students. These findings underscore the importance of incorporating motivational considerations into classroom assessment practices and call for professional development programs that equip teachers with strategies to support and evaluate student motivation effectively. The study contributes to the growing body of literature advocating for motivation-sensitive assessment systems, particularly in the Indonesian secondary education context.